2013
DOI: 10.1016/j.reprotox.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorodiphenyltrichloroethane (DDT), DDT metabolites and pregnancy outcomes

Abstract: Organochlorine pesticides (OCPs) are persistent endocrine disruptors. OCPs cross the placenta; this prenatal exposure has been associated with adverse pregnancy outcomes. We investigated associations between prenatal exposure to OCPs and gestational age and birth weight in 600 infants born between 1960 and 1963. The primary OCP was 1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane (p,p′-DDT), its primary metabolite, 1,1′-dichloro-2,2'-bis(p-chlorophenyl)ethylene(p,p′-DDE) and the contaminant, 1,1,1-trichloro-2-(p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 61 publications
3
34
1
3
Order By: Relevance
“…While DDT was used extensively from the 1940s until 1973, it is no longer in commercial use in the US, although it remains in the environment as a legacy contaminant [84]. Dichlorodiphenyldichloroethylene (DDE), a common breakdown product of DDT that may form in the environment or within the body, is often examined alongside DDT as it has been associated with adverse health outcomes in human populations [85,86]. While DDT and DDE both have long half-lives in the environment and the human body, DDE was observed to be the predominant form found in pregnant women participating in the National Health and Nutrition Examination Survey [87].…”
Section: Dichlorodiphenyltrichloroethanementioning
confidence: 99%
“…While DDT was used extensively from the 1940s until 1973, it is no longer in commercial use in the US, although it remains in the environment as a legacy contaminant [84]. Dichlorodiphenyldichloroethylene (DDE), a common breakdown product of DDT that may form in the environment or within the body, is often examined alongside DDT as it has been associated with adverse health outcomes in human populations [85,86]. While DDT and DDE both have long half-lives in the environment and the human body, DDE was observed to be the predominant form found in pregnant women participating in the National Health and Nutrition Examination Survey [87].…”
Section: Dichlorodiphenyltrichloroethanementioning
confidence: 99%
“…Interestingly, we also found that among smokers, the effect of 4-OH-CB107 on birth weight was opposite of the effect of its primary parent compound PCB118. The opposite effects of PCB118 and 4-OH-CB107 are similar to the effects of DDT, an organochlorine pesticide, where, when analyzed together, the parent compound, p,p′ -DDT, is positively associated with birth weight but the metabolite, p,p′ -DDE, is negatively associated [59]. The associations between PCB118, 4-OH-CB107, and birth weight, however, are distinct in the sense that they are restricted to smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is well acknowledged that perinatal exposure to these compounds occurs with influence in birth weight and later health outcomes [98][99][100][101][102][103]. The hormone-like activity of EDCs can disrupt the programming of endocrine signalling pathways that are established during perinatal differentiation, contributing to the development of obesity in adulthood.…”
Section: Endocrine Disruptors and In Utero Effectsmentioning
confidence: 99%